Laryngeal Inflammation: Diagnosis and Treatment Challenges. (23rd August 2013) - Fried, Marvin P.; Krouse, John H.; Altman, Kenneth W.; DelGaudio, John M.; Postma, Gregory N.
Abstract : Program Description: Using an interactive format, panelists will discuss epidemiology, symptomatology, and co‐morbid conditions contributing to laryngopharyngeal inflammation; diagnosis/differential diagnosis; challenges in diagnosing causative factors; addressing diagnostic challenges to define a treatment plan; current evidence; treatment challenges and impact of co‐morbid conditions; and future research and management implications. The panel will consider "real world" patient management algorithms. The audience will help answer the following questions: What are the typical 'challenges' in diagnosing laryngopharyngeal inflammation? What diagnostic testing options should be employed? Which after first treatment failure? What are the common treatment pathways? What differential data should be considered? What healthcare costs impact options? When is referral recommended? Educational Objectives: 1) Describe current practice trends on the diagnosis and management of laryngopharyngeal inflammation. 2) Recognize the common challenges in diagnosing laryngeal inflammation to define appropriate treatment strategies. 3) Evaluate current evidence‐based literature supporting current diagnosis and treatment paradigms.